Oral Levetiracetam as Add-On Therapy in Neonatal Seizures - Molla Mohammadi, Mohsen; Amirhoseini, Zeinab Sadat; Saadati, Alireza; Pirzadeh, Zahra; Hassanvand Amouzadeh, Masoud (Iranian Journal of Child Neurology, 2018)
Background: Seizure is the most common signs of nervous system disease in neonates.The first line of treatments in neonatal seizures (after ruling out and emergency treatment of electrolyte imbalance and hypoglycemia) are, phenobarbital and phenytoin. At least, 35%-45% of seizures may not be controlled by first-line drugs, so further treatment would be necessary. Levetiracetam has shown its safety and efficacy in treatment of neonatal seizures. We aimed to evaluate drugs that are more effective concerning neonatal seizure. Methods: Initially, 245 neonates presented with seizure in neonatal wards &NICUs(level IIa&IIb) in Qom hospitals,were enrolled in this clinical trial study(inclusion criteria). The main causes of seizure in 12 neonates were electrolyte imbalance and hypoglycemia,therefore, they were excluded from the study. Phenobarbital and then if needed, phenytoin administered to the remaining neonates, as first line treatment.Eventually, 42 neonates with a diagnosis of resistant seizure to these drugs were challenged with oral levetiracetam. Data was analysed using SPSS ver. 20.(Chicago,IL,USA). The study was registered as code number of IRCT2016051527896N1. Results: In this study,85.8% of seizures were controlled with initial dosage of oral levetiracetam and 9.5% by increasing the dose but 4.7% were not cured . Conclusion: when the intravenous form of levetiracetam is not available and neonatal seizure not respond to first line classic drugs,oral levetiracetam as add on therapy is effective. Keywords: Neonatal seizure, Oral levetiracetam, treatment